2018
DOI: 10.1177/0391560318772466
|View full text |Cite
|
Sign up to set email alerts
|

15 years’ survey of safety and efficacy of Serenoa repens extract in benign prostatic hyperplasia patients with risk of progression

Abstract: The 15 years' study results suggest that taking S. repens plant extract continuously at a daily dose of 320 mg is an effective and safe way to prevent the progression of benign prostatic hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 7 publications
(10 reference statements)
0
19
0
1
Order By: Relevance
“…This previous study also showed that Permixon treatment led to an improvement in LUTS symptoms, and an inhibition in the progression of BPH, that was equivalent to that achieved with a 6-month treatment with 5-ARIs (Vela-Navarrete et al, 2018). A 15-year open observation study investigated the changes in PV, Q-max, QOL, and IPSS, in BPH patients treated with a daily dose of S. palmetto extract (320 mg), and found that this extract was able to prevent the progression of BPH (Vinarov et al, 2019).…”
Section: Plant Extractsmentioning
confidence: 99%
“…This previous study also showed that Permixon treatment led to an improvement in LUTS symptoms, and an inhibition in the progression of BPH, that was equivalent to that achieved with a 6-month treatment with 5-ARIs (Vela-Navarrete et al, 2018). A 15-year open observation study investigated the changes in PV, Q-max, QOL, and IPSS, in BPH patients treated with a daily dose of S. palmetto extract (320 mg), and found that this extract was able to prevent the progression of BPH (Vinarov et al, 2019).…”
Section: Plant Extractsmentioning
confidence: 99%
“…In the extensive review of peer-reviewed literature on LSESr, a safety profile of high tolerability and low side effects has been a consistent finding. A collection of 50 articles focused on the safety and tolerability of LSESr, with eight having study durations ranging from two to fifteen years [23,27,29,[31][32][33][34][35]. Safety and tolerability of LSESr were never issues of concern as per the Cochrane reviews, multiple meta-analyses, and the EMA monograph.…”
Section: Lsesr Has a High Safety Profile In Contrast To Counterpart Prescription Drugsmentioning
confidence: 99%
“…The total number of patients involved in all 17 studies was 1,976. Two studies used a hypercritical CO2 extract of Serenoa repens (hCESr) [111,112], 5 studies employed a hexanic extract of Serenoa repens (HESr) [23,32,33,113], and 10 studies evaluated an ethanolic extract of Serenoa repens (EESr) [24,[27][28][29]31,34,35,107,114,115]. The average change in IPSS, QoL, and Qmax across all studies was -4.8, -1.6, and +3.0 ml/s, respectively.…”
Section: The Response To Lsesr Vs Luts Is Durablementioning
confidence: 99%
“…Цим аспектом виступає рівень небажаних побічних явищ (НЯ). Згідно даних 15-річного дослідження російських вчених, використання екстракту Serenoa repens є перспективним напрямком консервативного лікування ДГПЗ, із розвитком довгострокового ефекту покращення сечовипускання та відтермінування виникнення ускладнень у формі гострої затримки сечі [8].…”
Section: а к т у а л ь н ы е т е м ыunclassified